ANALISIS POTENSI PARIWISATA INDONESIA DALAM MENINGKATKAN PERTUMBUHAN EKONOMI: PERSEPSI PEDAGANG LOKAL TERHADAP DAMPAK WISATAWAN DALAM PENINGKATAN PENDAPATAN DI DANAU TOBA - Al-Bakry, M. Hafidh Nashiruddin (Pringgitan, 2023)
This study aims to analyze the potential of Indonesian tourism in increasing economic growth, with a focus on the perceptions of local traders on the impact of tourists in increasing income on Lake Toba. The research method used is structured interviews with local traders operating around Lake Toba. The results of the analysis show that local traders have different perceptions of the impact of tourists on their income. Most local traders see the arrival of tourists as an opportunity to increase their sales and income. The presence of tourists also triggers the development of the local economy as a whole, with a multiplier effect that benefits not only local traders, but also the communities and areas around Lake Toba. However, there are also some local traders who have a negative perception of the impact of tourists. They expressed fears of intensifying competition and concerns that local cultural authenticity might be eroded by the influence of mass tourism. It can be concluded that local traders around Lake Toba have various perceptions of the impact of tourists in increasing their income. Although there are some negative perceptions, such as increasingly fierce competition and concerns over the authenticity of local culture, positive perceptions are still more dominant. Local traders realize the importance of maintaining a balance between tourism growth and preserving the uniqueness and authenticity of local culture.Keywords:  Tourism Potential, Economic Development, Perceptions of Local Traders, Lake Toba